Cholesterol Modifies Nutritional Values and Flavor Qualities in Female Swimming Crab (Portunus trituberculatus) - Tingting Zhu; Min Jin; Hongyu Peng; Wenli Zhao; Yuedong Shen; Shichao Xie; Qicun Zhou (Aquaculture Nutrition)
The quality of crustacean aquatic products is affected by feed. Cholesterol (CHO), an essential element for crustacean growth, has been widely supplemented in diet, but its food quality regulation remains unclear. The study aimed to investigate the effects of different dietary CHO levels (0.12%, 1.00%, and 2.50%) on the nutritional value and flavor quality in the edible parts of female swimming crabs (Portunus trituberculatus). Results showed that dietary CHO levels significantly increased lipid content in the hepatopancreas and promoted the accumulation of n-3 long-chain polyunsaturated fatty acids (LC-PUFA) in the hepatopancreas and muscle by activating the gene expression related to biosynthesis pathways. However, with dietary CHO levels increased, protein content in muscle decreased significantly. This may be related to dietary CHO supplementation (especially 2.50% CHO level) suppressed amino acid accumulation in the hepatopancreas and muscle by downregulating the target of the rapamycin pathway and upregulating amino acid catabolism-related genes. Moreover, 1.00% CHO treatment had higher relative levels of volatiles, producing grassy, fruity, and fatty odors in muscle, which may be due to the upregulation of the branched-chain amino acid transaminase (bcat) expression level. Dietary CHO weakened nucleotide and free amino acid accumulation in hepatopancreas and muscle. Overall, this study suggests that dietary 1.00% CHO level had higher LC-PUFA and pleasing flavor substances in muscle but was not conducive to hepatopancreatic protein and flavor nucleotide deposition of swimming crab.